For a new political sociology : the relational approach of Pierre Bourdieu - Atkinson, Will, 1983- (Routledge, 2025)
This volume seeks to make the case for Pierre Bourdieu's relational sociology as a powerful, comprehensive and integrated paradigm for studying everything political.Bringing together a collection of experts writing on a wide range of topics organised into thematic sections, it not only shows that the applicability of Bourdieu's concepts is broader and more productive than previously thought, but it also demonstrates how Bourdieu's relational sociology advances on other perspectives and offers a 'joined-up' approach to the political, seamlessly capable of illuminating subjects as diverse as Brexit, voter choice, post-socialist transition, civil war, revolution, international relations and the structure of political science discourse itself.This collection will be essential reading for students and scholars of politics, whether they are sociologists, political scientists or international relations specialists.